The Role of Tiktok-Based Digital Marketing Strategy in Increasing Tour Package Sales at Geopark Ciletuh - Barliani Dewi Setyawati; Amanda Amanda (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The shift in tourist behavior from conventional information sources to digital platforms has pushed tourism businesses to adopt social media-based promotion strategies. This study examines the influence of TikTok on tour package sales at Geopark Ciletuh Sukabumi. A quantitative case study approach was employed with 120 respondents selected through purposive sampling. Data collection utilized questionnaires, interviews, and sales documentation. Validity and reliability tests were conducted before analyzing data using descriptive statistics and simple linear regression. The results show that TikTok has a positive and significant effect on purchase decisions with a significance value of 0.000 < 0.05 and a determination coefficient of 61.3%, indicating that TikTok contributes substantially to explaining consumer purchasing behavior. Tour package sales increased by 47% after the implementation of TikTok promotional strategies, demonstrating tangible business impact. The platform's visual and interactive nature enables destinations to showcase their attractions more engagingly, building consumer trust and interest through authentic user-generated content. Furthermore, TikTok's algorithm effectively targets relevant audiences, increasing content reach and engagement rates compared to traditional promotional methods. These findings confirm that TikTok serves as an effective digital marketing tool for tourism promotion, particularly in enhancing destination visibility and driving consumer purchasing decisions. This research provides practical implications for tourism stakeholders in developing cost-effective digital marketing strategies to adapt to evolving consumer preferences in the digital era.